2013
DOI: 10.1080/10511253.2012.730617
|View full text |Cite
|
Sign up to set email alerts
|

How to Write a Literature Review

Abstract: Learning how to effectively write a literature review is a critical tool for success for an academic, and perhaps even professional career. Being able to summarize and synthesize prior research pertaining to a certain topic not only demonstrates having a good grasp on available information for a topic, but it also assists in the learning process. Although literature reviews are important for one's academic career, they are often misunderstood and underdeveloped. This article is intended to provide both undergr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
61
0
31

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 184 publications
(136 citation statements)
references
References 5 publications
1
61
0
31
Order By: Relevance
“…The data was collected by applying recommended methodologies for conducting a literature review (Denney and Tewksbury, 2013). The papers were obtained using the search words "smart specialization" and "smart specialisation" for the abstract, title and keywords of studies in literature databases such as Scopus, EBSCO and ScienceDirect until the end of 2015.…”
Section: Methodsologymentioning
confidence: 99%
“…The data was collected by applying recommended methodologies for conducting a literature review (Denney and Tewksbury, 2013). The papers were obtained using the search words "smart specialization" and "smart specialisation" for the abstract, title and keywords of studies in literature databases such as Scopus, EBSCO and ScienceDirect until the end of 2015.…”
Section: Methodsologymentioning
confidence: 99%
“…The approach used in this study is a conceptual approach to literature study methods. This literature study uses various references in the form of journals, previous research, and documents as related data sources [14].…”
Section: Charismatic Leadershipmentioning
confidence: 99%
“…An integrative review is not a catalogue of past studies. A weak review strings together results in a way that reads like a list of annotations about individual studies (Denney & Tewksbury, 2013;Webster & Watson, 2002). There is no element of synthesis in "Study X showed A, study Y showed B, and study Z demonstrated C".…”
Section: Common Issues and Things To Avoidmentioning
confidence: 99%
“…But that does not make writing a good review paper easy; it requires substantial investment of time and thought, and a large dose of creativity. A good review paper not only summarises the current state of knowledge in a particular area, it also synthesises the literature to provide new insights and advance that field of research (Denney & Tewksbury, 2013;Pautasso, 2013;Torraco, 2005;Van Wee & Banister, 2016;Webster & Watson, 2002). So a good review is not just about looking back and summarising what has been done-it is about synthesising knowledge to show the way forward.There are very few general guidelines for how to write a good review paper because the format and structure are more flexible than that of a standard research paper.…”
mentioning
confidence: 99%